Role of Fintech in Driving Financial Inclusion: Evidence From Kaski - Kunwar, Kripa; Chhetri, Shanti Devi (The Batuk, 2025)
The advancement of financial technology (FinTech) introduces a new era of digital finance, a new avenue to increase access to finance for underprivileged and larger populations, emphasizing the importance of technological innovation in improving financial inclusion to achieve inclusive growth and financial stability. The study aims to investigate the factors influencing FinTech use and the impact of FinTech use on financial inclusion in Kaski, Nepal. A survey was administered to collect data from 261 samples in Kaski by following a convenience sampling method. The Partial Least Square Structural Equation Modelling (PLS-SEM) was employed to investigate the causal relationship between FinTech and financial inclusion. The findings show the positive effects of trust, service quality, and perceived security on FinTech adoption. Likewise, the study claims the significant positive impact of FincTech on financial inclusions. The study recognizes the role of FinTech on changing digital financial landscape to enhance the financial inclusion by removing various barriers. The findings of the study hold the significance for regulators and banking industry to reach out the exclusive sectors, address the weakness, and developing more financially inclusive society.